Begonia brunneosquamata (sect. Jackia, Begoniaceae), a new species from limestone karsts of Bolikhamxai Province, Central Laos - Phonepaseuth, Phongphayboun; Lin, Che-Wei (Phytotaxa, 2025)
Begonia brunneosquamata, a striking new species discovered in the limestone karst region of Bolikhamxai Province, central Laos, is described here. It resembles B. tatianae in being a rhizomatous plant with suborbicular leaves, 4-tepaled staminate flowers, and a zygomorphic androecium. However, the new species differs markedly from B. tatianae in several key morphological characters: the petioles and inflorescences are densely covered with scale-like brown trichomes (vs. glabrous), the anther apex is mucronate (vs. truncate), the pistillate flower bears five tepals (vs. four), and the ovary and styles are sparsely covered with scale-like brown trichomes (vs. ovary bearing sparse 3-branched purple trichomes and styles glabrous). Based on the currently available data, B. brunneosquamata is assigned to the Endangered (EN) category, following the Guidelines for Using the IUCN Red List Categories and Criteria.